2010
DOI: 10.1016/j.nimb.2009.10.056
|View full text |Cite
|
Sign up to set email alerts
|

BEAMS Lab at MIT: Status report

Abstract: The Biological Engineering Accelerator Mass Spectrometry (BEAMS) Lab at the Massachusetts Institute of Technology is a facility dedicated to incorporating AMS into life sciences research. As such, it is focused exclusively on radiocarbon and tritium AMS and makes use of a particularly compact instrument of a size compatible with most laboratory space. Recent developments at the BEAMS Lab were aimed to improve different stages of the measurement process, such as the carbon sample injection interface, the simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…This system and its operation have been described in detail in previous publications (42,43). Expired carbon dioxide that was trapped on Ascarite (Sigma) was analyzed after its release by treatment with concentrated sulfuric acid within a septumsealed vial and released carbon dioxide was introduced directly into the AMS source without laser combustion.…”
Section: Gas-fed 14 C-counting Ams Measurementsmentioning
confidence: 99%
“…This system and its operation have been described in detail in previous publications (42,43). Expired carbon dioxide that was trapped on Ascarite (Sigma) was analyzed after its release by treatment with concentrated sulfuric acid within a septumsealed vial and released carbon dioxide was introduced directly into the AMS source without laser combustion.…”
Section: Gas-fed 14 C-counting Ams Measurementsmentioning
confidence: 99%
“…In the case of high potency drugs, only the tritium‐labelled compound can give ADME information at the appropriate exposures, unless carbon‐14 accelerator mass spectrometry techniques are used. In this context, it is worth noting that accelerator mass spectrometry techniques are also applicable to the tritium isotope, resulting in ~1000‐fold increase in sensitivity over liquid scintillation counting …”
Section: Discussionmentioning
confidence: 99%
“…AMS does not quantify 8-oxodG directly, but is useful for metabolism studies in which a tracer of [ 14 C]8-oxodG or other related metabolites is tracked at physiologically relevant concentrations [1719]. A similar tracer study was reported for M 1 G metabolism [63] at the MIT BEAMS Lab [64]. Direct detection of DNA damage by AMS requires the utilization of specific "postlabeling" chemistries that are still in development for DNA adduct studies [55;65;66].…”
Section: Methods Of Analysismentioning
confidence: 99%